The Effect of Product Innovation and Brand Image on Purchase Intention of Citra Hand and Body Products in Surabaya - Ilmiah, Ismiatul; Wardhani, Nuruni Ika Kusuma (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
The skincare industry is one of the world's fastest expanding sectors, including in Indonesia. Skin care has become an integral part of the modern lifestyle, not only as an effort to maintain healthy skin, but also as a self-expression and confidence booster. Product innovation and brand image on Citra hand and body that is positive will build consumer confidence in the product or company. The intention of this study is to identify and analyze the impact of product innovation and brand image on purchasing interest in hand and body image items in Surabaya. This study makes use of primary data derived from questionnaire responses. The population of this study are people who live in Surabaya who know and know Citra hand and body products. The sample used was 84 respondents with purposive sampling technique. The results showed that product innovation and brand image have a significant positive effect on buying interest in Citra hand and body products in Surabaya.